"It Has a Way of Getting in Your Blood When You're Basque": Basque Sheepherders, Race, and Labor, 1880–1959. Issue 4 (19th August 2019) - Aquino, Mariel
Abstract: Despite their small numbers, Basque sheepherders became prototypical figures in the history the American West, viewed as elusive, mysterious men hidden in high pastures tending their enormous herds for months at a time. Basques became so associated with herding that even when the Immigration Act of 1924 placed severe restrictions on the number of Spanish nationals who could immigrate, American herders lobbied for special legislation that would allow them to keep importing sheepherders from Spain. This article contends that this preference for Basque herders arose not from Basques' particular expertise but from narratives of their ancient origins and racial distinctiveness. Both Basques and non-Basques developed constructions of Basqueness that emphasized the group's non-"Latin" status, thus placing Basques in an advantageous position in the American ethnoracial hierarchy relative to other Southern European ethnic groups. These narratives allowed sheepherding to be racialized as a Basque profession and also underlined Basques' European Indigeneity—an Indigeneity that was to some extent transferred to the American West.